一种稻蟹共生的种养方法 (2020)
本发明涉及农业种养殖技术领域，特别涉及一种稻蟹共生的种养方法；包括以下步骤：池塘改造、池塘处理、饵料培养、蟹苗培育、蟹苗日常管理、水稻种植、水稻田间管理、河蟹养殖；本发明形成水稻、河蟹、紫薯和/或紫苏以及多种水生植物、水生动物的微型生态圈，实现营养物质的互相补给互相支撑，有效的保证了水稻、河蟹的增产，通过生态圈之间的相互协调和控制，使得本发明的稻蟹共生的环境中将化肥，农药的使用率降到最低，减少了对环境的污染，同时也使得种植的水稻和河蟹安全、无激素，符合人们追求绿色食品的理念。 The invention relates to the technical field of agricultural planting and breeding and especially provides a novel planting-breeding method for rice and crab symbiosis. The method comprises the steps of: pond transformation, pond treatment, feed culture, juvenile crab cultivation, daily management of juvenile crabs, rice planting, field management for rice, and river crab breeding. With the method, a micro-ecosphere of rice, river crabs, purple sweet potatoes and/or purple perilla, as well as many other kinds of aquatic plants and aquatic animals is formed, so that mutual supply of nutrient substances and mutual support are achieved and yield increase of rice and river crabs is effectively guaranteed; through mutual coordination and control in the ecosphere, the rate of ut